Mini-invasive surgery for colorectal cancer - Zeng, Wei-Gen (Sun Yat-sen University Cancer Center, 2014)
Laparoscopic techniques have been extensively used for the surgical management of colorectal cancer during the last two decades. Accumulating data have demonstrated that laparoscopic colectomy is associated with better short-term outcomes and equivalent oncologic outcomes when compared with open surgery. However, some controversies regarding the oncologic quality of mini-invasive surgery for rectal cancer exist. Meanwhile, some progresses in colorectal surgery, such as robotic technology, single-incision laparoscopic surgery, natural orifice specimen extraction, and natural orifice transluminal endoscopic surgery, have been made in recent years. In this article, we review the published data and mainly focus on the current status and latest advances of mini-invasive surgery for colorectal cancer.